Pitch-based carbon/nano-silicon composite, an efficient anode for Li-ion batteries. Issue 19 (4th April 2019) - Escamilla-Pérez, Angel Manuel; Roland, Aude; Giraud, Sophie; Guiraud, Céline; Virieux, Héloïse; Demoulin, Kévin; Oudart, Yohan; Louvain, Nicolas; Monconduit, Laure
Abstract : Composites are prepared by simple mixture of laser pyrolysed silicon nanoparticles and petroleum pitch, a low cost carbon source. Helped by a homogeneous dispersion of Si nanoparticles into the pitch matrix high stability over cycling is observed. Abstract : As silicon–carbon electrodes with low silicon ratio are the negative electrode foreseen by battery manufacturers for the next generation of Li-ion batteries, a great effort has to be made to improve their efficiency and decrease their cost. Pitch-based carbon/nano-silicon composites are proposed as a high performance and realistic electrode material of Li-ion battery anodes. Composites are prepared in a simple way by the pyrolysis under argon atmosphere of silicon nanoparticles, obtained by a laser pyrolysis technique, and a low cost carbon source: petroleum pitch. The effect of the size and the carbon coating of the silicon nanoparticles on the electrochemical performance in Li-ion batteries is highlighted, proving that the carbon coating enhances cycling stability. Helped by a homogeneous dispersion of silicon nanoparticles into the amorphous carbon matrix, a high coulombic efficiency (especially in the first cycle) and a high stability over cycling is observed (over 1100 mA h g −1 after 100 cycles at relatively high current density 716 mA g −1 for Si based electrodes), which are superior to pitch-based carbon/silicon composites found in literature. This simple synthesis method may be extrapolated to other electrode active materials.